2009
DOI: 10.1186/1475-2875-8-11
|View full text |Cite
|
Sign up to set email alerts
|

Pfmdr1 copy number and arteminisin derivatives combination therapy failure in falciparum malaria in Cambodia

Abstract: Background: The combination of artesunate and mefloquine was introduced as the national firstline treatment for Plasmodium falciparum malaria in Cambodia in 2000. However, recent clinical trials performed at the Thai-Cambodian border have pointed to the declining efficacy of both artesunate-mefloquine and artemether-lumefantrine. Since pfmdr1 modulates susceptibility to mefloquine and artemisinin derivatives, the aim of this study was to assess the link between pfmdr1 copy number, in vitro susceptibility to in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
108
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 152 publications
(118 citation statements)
references
References 19 publications
10
108
0
Order By: Relevance
“…23 Similar findings of a reduced sensitivity to lumefantrine in vitro were described by Lim and others, 24 however, in that study the correlation could not be confirmed in vivo . Recently, it has been shown that pfmdr1 gene amplifications were absent from different study sites in PNG, including an area adjacent to our study site.…”
Section: Discussionsupporting
confidence: 71%
“…23 Similar findings of a reduced sensitivity to lumefantrine in vitro were described by Lim and others, 24 however, in that study the correlation could not be confirmed in vivo . Recently, it has been shown that pfmdr1 gene amplifications were absent from different study sites in PNG, including an area adjacent to our study site.…”
Section: Discussionsupporting
confidence: 71%
“…These differences may be related to different sampling times, different pharmacokinetic models, population variations in drug handling, and regional differences in susceptibilities in P. falciparum isolates to artemisinins and the partner drugs 36 in a region where recent data suggest that artemisinin resistance has developed. [40][41][42][43] It would seem that enrolment parasitemia significantly influenced the parasite clearance times. Thus, high parasitemias were associated with a longer parasite clearance times.…”
Section: Discussionmentioning
confidence: 99%
“…This achievement is owed to a rise in investments for vector control such as the use of Insecticide Treated Bed Nets (ITNs), and treatment including Intermittent Preventive Treatment during pregnancy (IPTp) and combined therapies, especially Artemisinin-Based Combined Therapies (ACTs) against uncomplicated malaria [6][7][8]. However, these successes are threatened by the emergence of parasite resistance against artemisinin [9][10][11]. Moreover, this resistance was firmly established in Cambodia, Thailand, Vietnam and Burma and its possible spread over the rest of South-east Asia has been documented [12,13].…”
Section: Introductionmentioning
confidence: 99%